Elucidation of the relationship between the electrochemical migration susceptibility of SnPb solders for PCBs and the composition of the resulting dendrites - Yoo, Y. R.; Kim, Y. S. (Metals and materials international, 2010)
Electrochemical migration occurs via electrochemical processes. When a water film forms on the electric circuit and then a bias voltage is applied, the metallic ions dissolve from the anode and move to the cathode. At the cathode, the metallic ions react with the electrons and then form dendrites. Thus, a short circuit failure of the electronic components occurs. This study focuses on the relationship between the electrochemical migration (ECM) susceptibility of SnPb solders and the composition of the dendrites on the basis of electrochemical techniques. It was found that the ECM susceptibility of SnPb solder alloys was affected by the chloride and sulfate ions. After the water drop test, the composition of the dendrites was primarily Pb mixed with Sn, regardless the dissolution/composition ratio of the solder alloys. However, only Sn was detected in the dendrites formed in the acidic solution. The dissolution of the metal from the anode influenced the failure time, and the pH of the corrosion environment significantly changed the composition of the dendrites formed on the cathode. The composition of the dendrites was proven to be closely related to the cathodic deposition efficiency of the ions dissolved from the anode.